Faktor-Faktor Yang Mempengaruhi Akuntabilitas Kinerja Instansi Pemerintah Provinsi Riau - Queen Shakira Az Zahra; Muhammad Ahyaruddin; Mentari Dwi Aristi (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of regulation, incentives, accounting control, organizational culture, and management commitment on the performance accountability of government agencies in Riau Province. A quantitative approach was applied by distributing questionnaires to 120 respondents consisting of echelon II, III, and IV officials. Data were analyzed using WarpPLS 7.0 through measurement model testing (outer model), structural model testing (inner model), and hypothesis testing. The results indicate that regulation, accounting control, organizational culture, and management commitment have a significant positive effect on performance accountability, while incentives exert a significant negative effect. The R-square value of 0.700 demonstrates that the independent variables explain 70% of the variance in performance accountability, with the remaining 30% influenced by other factors outside the model. These findings emphasize the critical role of consistent regulation, effective accounting control, supportive organizational culture, and strong management commitment in enhancing the performance accountability of government institutions.